(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Interaction of osteoblast-like Saos-2 cells with stainless steel and Si(100) covered by a film of densely intergrown silicalite-1 crystals is investigated. Surface properties of the films are tuned by synthesis conditions and post-synthetic modifications. A number of adhered cells is affected by surface morphology and wettability of the film.